Stanley Kubrick's 2001: a space odyssey : new essays - Kolker, Robert Phillip (Oxford University Press, 2006)
Almost all students have seen 2001, but virtually none understand its inheritance, its complexities, and certainly not its ironies. The essays in this collection, commissioned from a wide variety of scholars.